REPRESENTASI SISI KEMISKINAN DALAM FILM PARASITE (ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE) - Nada Amalia Zain; Dini Valdiani; Tiara Puspanidra (UNIVERSITAS PAKUAN, 2021)
Parasite (Korean: Gisaengchung) is a South Korean movie directed by Bong Joon-Ho. This movie, which is presented in 2019, is a dark humor film genre filled with tense scenes and dramas. Themes of social problems or problems that occur in South Korean society, namely poverty, are also presented in this movie. This research aims to analyze the poverty of a thriller drama movie. The meaning of poverty can be observed from several scenes through the relationship between signs and semiotic meanings using Charles Sanders Peirce's model with the concept of a triangle of meaning, namely sign, object and interpretant. Qualitative research in the form of Charles Sanders Peirce's semiotic analysis is used as a method in this research. Five of the entire scenes of the movie are selected as representations of poverty. The five scenes are analyzed through the relation of signs, objects and interpretant depicted in each scene. There are signs and meanings which describe poverty in several scenes in accordance with the type of poverty, namely relative poverty. The results of this study concluded that there are several scenes that represent poverty which is categorized into relative poverty as seen from the aspect of social inequality. This is because there are several characters who can make ends meet their minimum basic needs but they are still far lower than their surrounding society.